THE IMPLEMENTATION OF STAD (Student Team Achievement Division) AS COOPERATIVE LEARNING IN TEACHING READING OF NEWS ITEM TEXT TO ELEVENTH GRADE STUDENTS AT SMAN 1 KEDAMEAN (RETAIN, 2015)
English is an important and compulsory in High school since it is used as foreign language in Indonesia. In learning foreign language, there are four language skills that must be mastered by the students. One of the most important skills is reading. The aims of this study are to describe how the implementation of Student Team Achievement Division in teaching reading news item text to the students of eleventh graders, and to find out how the students’ response toward the implementation of Student Team Achievement Division is.This study is a descriptive qualitative research. The subject is the students of XI-MIA SMAN 1 Kedamean in the academic year 2014/2015. The instruments which are used in this study are observation checklist, field note, interview, Questionnaire. The researcher collects the data through observation in the classroom when the teaching learning process process, gave the students questionnaire and interview the teacher in the last meeting. The result of observations and interview are described in the form of words, The result of the study during observation show the students are able to implement the techniques. In the third meeting, they get higher score than the first score in the first meeting. The students point out that it is very useful to help them comprehend the text. In line with the result, Student Team Achievement Division can motivate the students and make them interested in reading.